Determining factor of continuous intention mobile payment: Using extending the unified theory of acceptance and use of technology (UTAUT2) model - Masyhuri Hamidi; Fajri Adrianto; Bryan Trianda Ginting (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2022)
This study aims to determine the Effect of Literacy Sharia, and Religiosity on the Intention to Use Islamic Mobile Payment with the Theory Of Planned Behavior approach. The object of the research study is the working-age community in the city of Padang and in the city of Bandar Lampung. The research method uses Multiple Linear Regression Analysis. The sampling technique used was the purposive sampling method with 150 respondents in each city. The main purpose of this study was to determine the comparison between the working-age community in the city of Padang and in the city of Bandar Lampung related to the intention to use Islamic mobile payment. Research data management was carried out using IBM SPSS 25. Data collection was carried out using online and/or offline questionnaires. The results of the study for the City of Padang showed that the variables of Sharia Literacy, Subjective Norms, and Control Perceptions had a significant effect on usage intention. Meanwhile, religiosity and attitude variables have no significant effect on the intention to use. Then, the results of the study for Bandar Lampung City showed that the variables of Subjective Norm and Perception of Control had a significant effect on intention in use, Meanwhile, the variables of Literacy Sharia, Religiosity, and Attitude had no significant effect on usage. Comparison of the level of intention in using Islamic m-payment for Padang City is 80.57% and Bandar Lampung City is 76.13% which is in the fairly high category. Therefore, the comparison between intention in using Islamic m-payment in Padang City is greater than in Bandar Lampung City. The results of this research can later be useful for m-payment service providers, knowledge for readers, and a source of information and reference for further research.